Long-term health outcomes and quality of life in women with untreated pelvic floor dysfunction: a single-center cohort study - Chen, Wenchao; Gong, Jiang; Liu, Mingsheng; Cai, Ying Chang (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to evaluate the long-term health outcomes and quality of life (HRQoL) associated with untreated pelvic floor dysfunction (PFD) in women, and to identify key factors contributing to symptom severity.MethodsA cohort of 1,651 women aged 18 years and older with untreated PFD were recruited between June 2018 and August 2023. Data on sociodemographic, lifestyle factors, and clinical history were collected via questionnaires and clinical assessments. The Pelvic Floor Distress Inventory (PFDI-20) and Short Form-12 (SF-12) were used to assess symptom severity and HRQoL.ResultsThe study found that 56% of participants experienced urinary incontinence (UI), 52% had pelvic organ prolapse (POP), and 47% reported gynecological disorders. Sleep apnea (OR: 18.3, p < 0.001) and menopause (OR: 2.48, p < 0.001) were significantly associated with higher symptom severity, while postpartum complications had a protective effect (OR: 0.01, p < 0.001). Obesity was inversely associated with symptom severity (OR: 0.3, p < 0.001). HRQoL scores showed that 97.6% of participants had high physical functioning (mean PF: 67.36 ± 11.62), but vitality (VT) was notably lower, with 27.8% scoring below 50 (mean VT: 54.84 ± 6.60). FI (p = 0.006) and pelvic pain (p = 0.001) were linked to significantly poorer physical functioning and higher bodily pain.ConclusionUntreated PFD has a profound impact on HRQoL, especially in women with sleep apnea, menopause, and pelvic pain. Early diagnosis and intervention are critical to mitigating these effects and improving long-term outcomes. These findings highlight the urgent need for targeted public health strategies to address untreated PFD.